2022
DOI: 10.1002/pon.5905
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychosocial variables in breast self‐examination practice: Results from focus group discussions in Surabaya, Indonesia

Abstract: Introduction: Breast cancer is a global life-threatening disease. Breast selfexamination (BSE) followed by timely diagnosis and treatment is a viable screening method for populations with limited health care access such as Indonesia.Knowledge of the beliefs underlying BSE could benefit the development of future health education efforts to promote BSE and breast cancer awareness among Indonesian women, with the ultimate aim to achieve early detection and promote long-term survivals. The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
2
0
3
Order By: Relevance
“…14 En cuanto a las actitudes sobre el autoexamen de mamas, la mayoría refirieron estar de acuerdo en que es bueno realizarlo, ayuda a detectar el cáncer en sus inicios, tiene muchos beneficios para la salud, hallazgos que concuerda al de otras investigaciones. 9,15,16 Además, la mayoría de las mujeres están de acuerdo en que les preocupa la aparición de bultos y sentir miedo de realizarlo. Este resultado coincide al encontrado en Ecuador 15 y al hallazgo de Indonesia, 16 donde las mujeres manifestaron miedo a autoexaminarse y descubrir algún bulto.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…14 En cuanto a las actitudes sobre el autoexamen de mamas, la mayoría refirieron estar de acuerdo en que es bueno realizarlo, ayuda a detectar el cáncer en sus inicios, tiene muchos beneficios para la salud, hallazgos que concuerda al de otras investigaciones. 9,15,16 Además, la mayoría de las mujeres están de acuerdo en que les preocupa la aparición de bultos y sentir miedo de realizarlo. Este resultado coincide al encontrado en Ecuador 15 y al hallazgo de Indonesia, 16 donde las mujeres manifestaron miedo a autoexaminarse y descubrir algún bulto.…”
Section: Discussionunclassified
“…9,15,16 Además, la mayoría de las mujeres están de acuerdo en que les preocupa la aparición de bultos y sentir miedo de realizarlo. Este resultado coincide al encontrado en Ecuador 15 y al hallazgo de Indonesia, 16 donde las mujeres manifestaron miedo a autoexaminarse y descubrir algún bulto. En consecuencia, estas actitudes son significativas ante la incidencia del carcinoma de mama en mujeres jóvenes incluso cuando se conoce que en estos grupos etarios son más vulnerables y es el principal origen de muerte por cáncer.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…For example, the findings of a study in Iran showed that perceived barriers, knowledge and level of education were related to BSE. The results of Dewi et al [ 59 ] study in Surabaya indicated that breast cancer knowledge and attitudes toward BSE were associated with performing BSE. Also, perceived benefits and barriers and subjective norms were significantly related to the intention and doing of BSE.…”
Section: Discussionmentioning
confidence: 99%
“…The included research showed that various social media outlets could raise the degree of women's health promotion [ 25 ], awareness of menstrual hygiene, understanding of breast cancer awareness [ 26 ], breastfeeding techniques [ 27 ], and adherence, self-perception and promotion of oral health [ 28 , 29 ], significant use of antibiotics [ 30 ], consistency with exercise, sexual health promotion [ 31 ], road safety awareness [ 32 ], smoking cessation, adverse drug reaction reporting [ 33 ], and many more in a row.…”
Section: Reviewmentioning
confidence: 99%